2016
DOI: 10.1016/j.aej.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Bench-scale packed bed sorption of Cibacron blue F3GA using lucrative algal biomass

Abstract: Adsorption of Cibacron blue F3GA (Reactive Blue 2) onto Spirulina platensis has been investigated in both batch mode and packed bed up-flow column. The effects of solution pH, initial dye concentration, particle size and temperature were studied in batch mode and the optimal conditions were used in continuous mode. The algal biomass revealed maximum dye uptake in acidic pH at room temperature. The breakthrough curves were obtained for various flow rates (4, 8 and 12 ml/min) and bed heights (5, 7.5 and 10 cm). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 23 publications
2
1
0
1
Order By: Relevance
“…As regards the bed height, qe increased with an increase in bed height, this is because at higher bed height the phenolic ions have more available active sites for sorption, thereby leading to an increase in the adsorption capacity. The trend of the relationship between the adsorption capacity and the process variables obtained in this study is similar to the trend reported by Shanmugamet al [58] in a similar study. The high correlation coefficient values (R 2 > 0.9) obtained in the analysis in most cases showed that the Thomas model fitted the experimental data quite well.…”
Section: 31thomas Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…As regards the bed height, qe increased with an increase in bed height, this is because at higher bed height the phenolic ions have more available active sites for sorption, thereby leading to an increase in the adsorption capacity. The trend of the relationship between the adsorption capacity and the process variables obtained in this study is similar to the trend reported by Shanmugamet al [58] in a similar study. The high correlation coefficient values (R 2 > 0.9) obtained in the analysis in most cases showed that the Thomas model fitted the experimental data quite well.…”
Section: 31thomas Modelsupporting
confidence: 92%
“…index to investigate the internal structure and surface area of the activated carbon [57]. Shanmugamet al [58] noted that the carbonization and activation process conditions are not the only major contribution towards the porous structure of activated carbon but also being influenced by the original nature and structure of the starting material.…”
Section: Physical Properties Bet Surface Area and Pore Size Distribmentioning
confidence: 99%
“…The broad peak of O-H stretching vibration of CB-F3GA@mPHEMA monomer at 3448 cm -1 has disappeared after adsorption CB-F3GA@mPHEMA. FTIR analysis of same polymer is supported with our studies [29,[34][35][36].…”
Section: Ftir Analysissupporting
confidence: 80%
“…Both external (fluid-film) and intraparticle (solid) mass-transfer resistance were ignored in the Thomas model. This indicates that the surface reaction between the adsorbate and the unused capacity of the adsorbent controlled the adsorption rate [73]. The kinetic constant values, K Th , reduced as the bed height increased because the adsorbent-adsorbate interactions could occur faster in a greater amount of adsorbent.…”
Section: Breakthrough Curve Modellingmentioning
confidence: 99%